Functional traits of the invasive species Thunbergia alata (Acanthaceae) and its importance in the adaptation to Andean forests - Quijano-Abril, Mario Alberto; Castaño López, Maria de los Ángeles; Marín-Henao , Daniela; Sánchez-Gómez, David Alejando; Rojas-Villa, Jose Miguel; Sierra-Escobar, Jorge (Instituto de Ecología, A.C., 2021)
Background and Aims: Thunbergia alata is one of the ten most problematic invasive plant species in Colombia. Its rapid colonization and adaptation to Andean forests have affected the composition and structure of indigenous plant communities. In this research, analysis of functional traits was carried out, generating new information that could explain the rapid colonization, adaptation and invasive potential of T. alata in this type of Andean environment. Methods: To obtain this information, a series of observations were made on the morphology and anatomy of roots, stems, leaves, flowers, fruits and seeds. Likewise, a characterization of its floral visitors and symbiotic relationships with soil microorganisms was carried out. Key results: We determined that both morphological traits and interaction phenomena favour the adaptability of T. alata in Andean forests and could contribute to a greater extent to its active colonization in this type of environment. An active association of T. alata was found with different species of native and introduced floral visitors, with a total of 2266 floral visits made during our study by seven species of insects belonging to the orders Coleoptera and Hymenoptera. Mycorrhizal fungal spores associated with T. alata populations were found at all sampling sites. The number of spores per 100 g of soil varied between 300 and 424. All the roots of T. alata, without exception, had high colonization by arbuscular mycorrhizal fungi. Conclusions: We believe that the information obtained in this research will contribute to the generation of comprehensive and effective strategies for the control of this species in Andean forests.